Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2007
DOI: 10.1145/1240624.1240742
|View full text |Cite
|
Sign up to set email alerts
|

Comparing physical, automatic and manual map rotation for pedestrian navigation

Abstract: It is well-established finding that people find maps easier to use when they are aligned so that "up" on the map corresponds to the user's forward direction. With mapbased applications on handheld mobile devices, this forward/up correspondence can be maintained in several ways: the device can be physically rotated within the user's hands or the user can manually operate buttons to digitally rotate the map; alternatively, the map can be rotated automatically using data from an electronic compass. This paper exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…Using integrated compasses embedded within a mobile device, Forward-up maps have helped to ease the challenges of mental rotation by continually keeping the map on a digital device aligned with the direction the device is pointed. Studies have found this greatly improves navigational performance when compared against North-up maps where the map itself is always aligned so that geographic north is pointed towards the top of the map (Hermann et al, 2003;Seager and Fraser, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using integrated compasses embedded within a mobile device, Forward-up maps have helped to ease the challenges of mental rotation by continually keeping the map on a digital device aligned with the direction the device is pointed. Studies have found this greatly improves navigational performance when compared against North-up maps where the map itself is always aligned so that geographic north is pointed towards the top of the map (Hermann et al, 2003;Seager and Fraser, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It can be countered by physically aligning the map with the environment, as shown in Figure 1. Doing so eases their interpretation [15]. In this paper we investigate a different approach to simplify the interpretation of paper maps.…”
Section: Introductionmentioning
confidence: 99%
“…However, this type of map was problematic during this experiment when operators had to attend to a driving camera display and did not have the opportunity to pay constant attention to the map display. Seager and Stanton-Fraser (2007) found this to be true when their experiment demonstrated that users find it difficult to recognize a map that rotates automatically when they are not looking at the map. The addition of a tactile navigation display would alleviate this problem.…”
Section: Discussionmentioning
confidence: 97%